CRISPR screening identifies T cell-intrinsic regulators of CD3-bispecific antibody responses - Molony, Ryan D.; Funk, Theresa; Trabucco, Gina; Corcoran, Erik; Ruddy, David; Varadarajan, Malini; Elliot, GiNell; Piquet, Michelle; Lam, Joni; Meyer, Matthew J.; Wang, Hui Qin; Kurtulus, Sema; et al. (Frontiers in Immunology, 2022)
CD3-engaging bispecific antibodies (BsAbs) enable the formation of an immune synapse between T cells and tumor cells, resulting in robust target cell killing not dependent on a preexisting tumor specific T cell receptor. While recent studies have shed light on tumor cell-specific factors that modulate BsAb sensitivity, the T cell-intrinsic determinants of BsAb efficacy and response durability are poorly understood. To better clarify the genes that shape BsAb-induced T cell responses, we conducted targeted analyses and a large-scale unbiased in vitro CRISPR/Cas9-based screen to identify negative regulators of BsAb-induced T cell proliferation. These analyses revealed that CD8+ T cells are dependent on CD4+ T cell-derived signaling factors in order to achieve sustained killing in vitro. Moreover, the mammalian target of rapamycin (mTOR) pathway and several other candidate genes were identified as intrinsic regulators of BsAb-induced T cell proliferation and/or activation, highlighting promising approaches to enhancing the utility of these potent therapeutics.